2018
DOI: 10.1097/pts.0000000000000178
|View full text |Cite
|
Sign up to set email alerts
|

Do Written Disclosures of Serious Events Increase Risk of Malpractice Claims? One Health Care System's Experience

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…Research suggests that disclosing errors of which patients are unaware does not lead to more malpractice cases. [37][38][39][40] It seems unlikely that gathering patient and family reports of errors of which patients are already aware would increase malpractice risk. Moreover, engaging patients and families may drive hospitals to bridge the gap between safety reporting and improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research suggests that disclosing errors of which patients are unaware does not lead to more malpractice cases. [37][38][39][40] It seems unlikely that gathering patient and family reports of errors of which patients are already aware would increase malpractice risk. Moreover, engaging patients and families may drive hospitals to bridge the gap between safety reporting and improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 717 completed FSIs. Their median (interquartile range) age was 32.5 (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) years; 380 (53.0%) were nonwhite, 566 (78.9%) were female, 603 (84.1%) were English speaking, and 380 (53.0%) had attended college. Of 717 parents/caregivers completing FSIs, 185 (25.8%) reported a total of 255 incidents, which were classified as 132 safety concerns (51.8%), 102 nonsafety-related quality concerns (40.0%), and 21 other concerns (8.2%).…”
Section: Main Outcomes and Measures-error And Ae Ratesmentioning
confidence: 99%
“…Physicians are concerned that if compensation is given, there will be increase reporting to the NPDB and increase insurance premiums. In a study of implementation of a bill requiring disclosure of error in Pennsylvania in 2009, Painter et al 20 showed an increase in amount of compensation with disclosure compared to similar claims when disclosure did not occur. However, no CRP was known to occur in Pennsylvania during the study period.…”
Section: Resultsmentioning
confidence: 99%
“…The implementation of this act was not associated with an increase in medical malpractice claims. 51 In 2001, the University of Michigan Health System (UMHS) implemented a program mandating full disclosure of medical errors to patients along with prompt compensation. Since the implementation of this program, UMHS has experienced a significantly decreased rate of malpractice claims, total payouts, and liability cost.…”
Section: Ethical Considerationsmentioning
confidence: 99%